2007
DOI: 10.1111/j.1364-3703.2007.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

The mixed xylem sap proteome of Fusarium oxysporum‐infected tomato plants

Abstract: SUMMARY Secreted proteins are known to play decisive roles in plant-fungus interactions. To study the molecular details of the interaction between the xylem-colonizing, plant-pathogenic fungus Fusarium oxysporum and tomato, the composition of the xylem sap proteome of infected tomato plants was investigated and compared with that of healthy plants. Two-dimensional gel separation and mass spectrometry yielded peptide masses and peptide sequences of 33 different proteins. Despite the absence of complete genome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
268
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(274 citation statements)
references
References 32 publications
4
268
0
2
Order By: Relevance
“…We did notice that SIX1 and the other known SIX genes (SIX2, SIX3 and SIX4, all encoding small proteins secreted in xylem during infection) share some common characteristics in the promoter (Houterman et al, 2007). In or close to each of the promoters a transposon (miniature impala) is present and each contains a variant of the motif 'TCGGCAGTTW'.…”
Section: Discussionmentioning
confidence: 96%
“…We did notice that SIX1 and the other known SIX genes (SIX2, SIX3 and SIX4, all encoding small proteins secreted in xylem during infection) share some common characteristics in the promoter (Houterman et al, 2007). In or close to each of the promoters a transposon (miniature impala) is present and each contains a variant of the motif 'TCGGCAGTTW'.…”
Section: Discussionmentioning
confidence: 96%
“…Ralstonia solanacearum (Smith) Yabuuchi et al (Dahal et al, 2009), Tobacco mosaic virus (Casado-Vela et al, 2006), Clavibacter michiganensis subsp. michiganensis (Smith) Davis et al (Savidor et al, 2012) or Fusarium oxysporum (Houtermann et al, 2007), thereby pointing to an involvement of PR-2 proteins in the expression of the resistance. On the other hand, data from a recent comparative proteomic investigation on FORL infection of roots in resistant and susceptible tomato lines, showed that b-1,3-glucanases and endochitinases were accumulated only in susceptible plants (Mazzeo et al, 2014), thus suggesting that PR-2 or PR-4 proteins in resistant lines are not essential to the defense response.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, functional approaches, including proteomics, have greatly contributed to the molecular dissection of plantepathogen interactions, allowing to identify a number of defence-related candidate proteins and helping to clarify specific gene expression patterns (Metha et al, 2008). In tomato, proteomic studies have been performed to investigate response to bacteria (Afroz et al, 2009;Dahal et al, 2010;Savidor et al, 2012), virus (Casado-Vela et al, 2006) and fungi (Houtermann et al, 2007;Mazzeo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium mycotoxins such as deoxynivalenol, nivalenol, T2, zearelenone, fusaric acid, moniliformin, etc... have adverse effects on both human and animal health and some are considered as pathogenicity factors. Proteomic studies showed to be effective for deciphering toxin production mechanisms (Taylor et al, 2008) as well as for identifying potential pathogenic factors (Paper et al, 2007, Houterman et al, 2007 in Fusaria. It becomes therefore fundamental to establish reliable methods for comparing between proteomic studies in order to rely on true differences found in protein expression among experiments, strains and laboratories.…”
Section: Introductionmentioning
confidence: 99%